The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41409-022-01680-z
|View full text |Cite
|
Sign up to set email alerts
|

Controversies about immunoglobulin replacement therapy in HSCT recipients with hypogammaglobulinemia

Abstract: The efficacy of immunoglobulin replacement therapy (IgRT) has been demonstrated for primary immune deficiency diseases and hematological malignancies such as chronic lymphocytic leukemia (CLL) or multiple myeloma with hypogammaglobulinemia. Clinical development of anti-B cell therapies including a monoclonal antibody, bispecific antibody, or chimeric antigen receptor T-cell therapy which could result in severe hypogammaglobulinemia accelerates the argument of prophylactic use of IgRT. Clinical guidelines for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…4. Immunoglobulin replacement: Data on immunoglobulin replacement in CAR T-cell therapy is extrapolated from patients with hematologic malignancy who receive anti-CD20 monoclonal antibody and patients who undergo allogeneic HSCT [96][97][98][99]. Therefore, it is unclear if IVIG replacement alters the overall post-CAR T-cell IgG level or improves survival outcomes [96,100].…”
Section: Antibacterial Prophylaxis: As Risk Of Bacterial Infectionmentioning
confidence: 99%
“…4. Immunoglobulin replacement: Data on immunoglobulin replacement in CAR T-cell therapy is extrapolated from patients with hematologic malignancy who receive anti-CD20 monoclonal antibody and patients who undergo allogeneic HSCT [96][97][98][99]. Therefore, it is unclear if IVIG replacement alters the overall post-CAR T-cell IgG level or improves survival outcomes [96,100].…”
Section: Antibacterial Prophylaxis: As Risk Of Bacterial Infectionmentioning
confidence: 99%
“…Data on ScIgRT in the field of allo-HCT are limited, as reviewed previously. 15 In a recent small study, ScIg was administered to allo-HCT patients for up to 6 months, with no statistically significant benefit in clinical outcomes but an advantage in terms of patient satisfaction and healthcare costs. 21 The small number of patients and short duration of intervention in that pilot study may have been insufficient to assess the incidence and severity of infections.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] However, it is not well established whether hypogammaglobulinaemia in allo-HCT recipients affects clinical outcomes, including the incidence of infectious diseases. 15 One prospective RCT revealed the marked utility of IgRT in allo-HCT. 16 Although other studies also assessed the beneficial impact of IgRT after allo-HCT, meta-analyses showed no consistent benefit to using IgRT after allo-HCT.…”
Section: O R I G I N a L P A P E Rmentioning
confidence: 99%
See 2 more Smart Citations